Intercultural Usage of Mori Folium: Comparison Review from a Korean Medical Perspective. (11th October 2015) - Joh, Byungjin; Jeon, Eun Sang; Lim, Su Hye; Park, Yu Lee; Park, Wansu; Chae, Han
Abstract : Objectives . A review on studies related to the use of Mori folium, the leaves of Morus alba, was conducted with the goal of identifying new clinical applications in Korean medicine. Methods . Global literature search was conducted using three electronic databases up to January 2015 with the term Morus alba and its Korean terms. KM literatures including textbooks and standard pharmacopoeia were separately hand-searched and reviewed to provide comparison. Data were extracted according to predetermined criteria, and clinical uses were standardized with ICD-10 categories. Results . 159 potentially relevant studies were identified, and 18 articles including 12 ethnopharmacologic and 6 clinical studies were finally included in this analysis. Ethnopharmacologic studies from 8 countries provided 17 clinical uses. We found that five out of six clinical trials were related to diabetes and suggested a moderate short-term to mild long-term effect. And 43 Korean texts also provided 156 clinical uses in 35 categories including ocular and respiratory disorders. Discussion and Conclusions . Though majority of the clinical uses were also found in Korean medicine literature, treatment of infertility, jaundice, cognitive disorder, and hyperpigmentation was found to be effective and diabetes with Morus alba was recognized to have clinical importance.